Students’ Spatial Reasoning in Solving Geometrical Transformation Problems - Serli Evidiasari; Subanji Subanji; Santi Irawati (Universitas Muhammadiyah Surakarta, 2019)
This study describes spatial reasoning of senior high school students in solving geometrical transformation problems. Spatial reasoning consists of three aspects: spatial visualization, mental rotation, and spatial orientation. The approach that is used in this study is descriptive qualitative. Data resource is the test result of reflection, translation, and rotation problems then continued by interview. Collecting data process involves 35 students. They are grouped to three spatial reasoning aspects then selected one respondent to be the most dominant of each aspect. The results of this study are: (1) the students with spatial visualization aspect used drawing strategy and non-spatial strategy in solving geometrical transformation problems. She transformed every vertex of the object and drew assistance lines which connect every vertex of the object to center point; (2) the students with mental rotation aspect used holistic and analytic strategies in solving geometrical transformation problems. Using holistic strategy means imagining the whole of transformational objects to solve easy problems. While using analytic strategy means transforming some components of objects to solve hard problems; (3) the students with spatial orientation didn’t involve mental imagery and she only could determine the position and orientation of the object in solving geometrical transformation problems